Semantic Imprecision in the 2019 Indonesian Ministry of Religious Affairs' Qur'an Translation: An Asbab al-Nuzul, Lexicographical, and Classical Tafsir Analysis of QS an-Nur [24]: 26 - Mutaqillah Ahmad; Ahmad Nur Fathoni; Kharis Nugroho; Andri Nirwana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The 2019 Revised Edition of the Indonesian Ministry of Religious Affairs' Qur'an translation occupies a central place in shaping the religious understanding of Indonesian Muslims, so that each of its lexical choices carries wide consequences. This article examines a problem that has not been systematically addressed in the existing critique of the official translation, namely the mismatch between the asbab al-nuzul context and the chosen translational equivalents. The problem is illustrated through a single, highly representative case: QS an-Nur [24]: 26, revealed within the episode of the Hadith al-Ifk. This is a qualitative library research that applies a layered analytical model integrating classical asbab al-nuzul reports (al-Wahidi and al-Suyuti), classical Arabic lexicography (al-Raghib, Ibn Manzur, Ibn Faris), and classical exegesis (al-Tabari, al-Zamakhshari, al-Razi, Ibn Kathir, al-Qurtbi). The findings show that the Ministry renders al-khabithat lil-khabithin in a literal-biological sense (“wicked women for wicked men”), whereas the intratextual context and the majority of classical exegetes support the al-kalimat reading (“evil speech befits evil people”). The literal rendering severs the verse from the slander episode that occasioned its revelation and shifts its message from the domain of speech to that of marriage. The study concludes that, although the 2019 translation remains commendable, this verse requires either an interpretive (tafsiriyah) strategy or an optimisation of historical-contextual footnotes. Theoretically, the article proposes asbab al-nuzul as an operational parameter for evaluating Qur'anic translation.